(3cJGH aj GdfMhs - (3WGgQ Hf CMeO Hf HGH TGP, GdeUQj GdLhgQj, CHh GdMSf,J (B469 (3g` s
(3ChdgG (B:s
(3bGd GdTjN CHh GdMSf WGgQ Hf CMeO Hf HGHTGP GdfMhi bGd GdfMh Yde eSJfHW HGdbjGS hGdESJbQGA ef cJGH Gddg JYGdi hGdcdGe GdaUM hGdZQV Hg s
(3BNQgG (B:s
(3abWY GdMQcI gh GdCUd jchf ai GdCaYGd GdUMjMI Ydi s
(3GdfSNI HgG MhGTs
(3HBNQg LRA ef cJGH BNQ ai GdfMhs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B220 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B32s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdfMhs